Assessment of deterioration in RHA-concrete due to magnesium sulphate attack - Habeeb, G.A.; Mahmud, H.B.; Hamid, N.B.A.A. (Springer Verlag (Germany), 2010)
The assessment of magnesium sulphate attack on concretes containing rice husk ash (RHA, 20wt% of the cementitious materials) with various average particle sizes was investigated. The total cementitious materials were 390 kg and the water-to-binder ratio (W/B) was 0.53 for all mixtures. Specimens were initially cured in water for 7 d and then immersed in the 3wt% magnesium sulphate solution for up to 111 d of exposure. The specimens were subjected to drying-wetting cycles to accelerate sulphate attack. In addition to the visual monitoring of the specimens, the concrete specimens were subsequently tested for compressive strength, dynamic modulus of elasticity, and length and mass changes. The results show that the specimens exposed to sulphate attack exhibit higher strength and dynamic modulus than those kept in water. The length change is negligible and can be attributed to the normal swelling of concrete. On the other hand, concretes suffers mass loss and surface spalling and softening; the fine RHA-concrete results in a better resistance. For the accelerated sulphate attack method used in this study, mass change and visual monitoring are recommended for assessing the deterioration degree and the effectiveness of supplementary cementitious materials to resist sulphate attack.